Direitos Humanos e tutela jurídica do idoso: violência financeira contra a pessoa idosa na comarca de Porto Nacional – TO - Lima, José Maria (Universidade Federal do Tocantins, 2019)
Human aging is a very recent phenomenon, but it already causes many reflexes in the most varied sectors of our contemporary society, since it increases rapidly and almost without social or governmental control, imposing on all, society or governments, the urgent search for means so that today a considerable part of the population is not demeaned in their rights and dignity. In the present research the diverse definitions of human rights were searched, as well as to insert the violence, in all its shades, as capable of damaging such rights. There were several types of violence practiced against the elderly, and among them, the most notable is the financial violence that has spread almost uncontrollably in the social and home environment of those who are already achieved by the age of 60 years or more. Given this context, this study attempted to identify the occurrence of such a type of violence in the Region of Porto Nacional, State of Tocantins, during the year 2017. The research was qualitative and quantitative focused on ongoing or completed lawsuits that were filed with the Second Civil Court and the Special Civil Court of the mentioned county. The data collected and analyzed showed that in 81% of the cases filed with the Second Civil Court, and in 58% of those existing with the Special Civil Court, men were victims, with a higher percentage in the age group from 60 to 69 years (57%). Among the agents responsible for financial violence against the elderly, at the Second Civil Court, 38% were public bodies and 33% were from financial institutions, and with the Special Court, the overwhelming majority, 65%, were the author of fact a financial institution. It was not possible to have access to the similar procedures promoted by the Nucleus of Procon based in Porto Nacional, which in a way imposed a limitation to the research. From the above context, it is evident the importance of the present research and its contribution to the elaboration of measures that aim to curb and punish this type of violence, causing society, in general, as well as the government agencies can to implement measures that bring about a true cultural change in the way of thinking and acting in relation to treatment with the elderly, because legislation alone does not have the capacity to change paradigms and behaviors. It is necessary, then, an educational process capable of forming cultural and social awareness in relation to the problem faced, so that even the elderly person himself becomes aware of his rights and demands respect for this part of the population.